2003
DOI: 10.1523/jneurosci.23-09-03953.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Within-Subjects, Within-Task Demonstration of Intact Spatial Reference Memory and Impaired Spatial Working Memory in Glutamate Receptor-A-Deficient Mice

Abstract: Gene-targeted mice lacking the AMPA receptor subunit glutamate receptor-A (GluRA) (GluR1) and wild-type controls were compared on a radial-maze task in which the same three of six arms were always baited, but in which the rewards of milk were not replaced within a trial. This procedure allowed not only a within-subjects but also a within-trials assessment of both spatial working memory (WM) and reference memory (RM) in GluRA Ϫ/Ϫ mice, using identical spatial cues. In experiment 1, the GluRA Ϫ/Ϫ mice made more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
173
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(188 citation statements)
references
References 30 publications
8
173
3
Order By: Relevance
“…Whereas mice with hippocampal lesions are impaired on both spatial working memory (SWM) and spatial reference memory (SRM) tests, genetically modified mice lacking the glutamate receptor-A (GluR-A; also known as GluR1) AMPA receptor subunit (GluR-A Ϫ/Ϫ mice), which is required for long-term potentiation (LTP) expression in adult mice (Zamanillo et al, 1999;Hoffman et al, 2002;Malinow and Malenka, 2002;Jensen et al, 2003), display a strikingly different phenotype. They exhibit normal hippocampus-dependent SRM performance on a number of tasks, including the water maze, while being profoundly impaired on hippocampus-dependent SWM tasks (Reisel et al, 2002;Schmitt et al, 2003Schmitt et al, , 2005. These results suggest that there are two spatial information-processing mechanisms, both dependent on the hippocampus for expression, but supported by distinct molecular pathways.…”
Section: Introductionmentioning
confidence: 83%
“…Whereas mice with hippocampal lesions are impaired on both spatial working memory (SWM) and spatial reference memory (SRM) tests, genetically modified mice lacking the glutamate receptor-A (GluR-A; also known as GluR1) AMPA receptor subunit (GluR-A Ϫ/Ϫ mice), which is required for long-term potentiation (LTP) expression in adult mice (Zamanillo et al, 1999;Hoffman et al, 2002;Malinow and Malenka, 2002;Jensen et al, 2003), display a strikingly different phenotype. They exhibit normal hippocampus-dependent SRM performance on a number of tasks, including the water maze, while being profoundly impaired on hippocampus-dependent SWM tasks (Reisel et al, 2002;Schmitt et al, 2003Schmitt et al, , 2005. These results suggest that there are two spatial information-processing mechanisms, both dependent on the hippocampus for expression, but supported by distinct molecular pathways.…”
Section: Introductionmentioning
confidence: 83%
“…As such, these data build upon an elegant series of studies demonstrating selective performance deficits on tests for working memory and cognitive flexibility, behaviors that are also impaired in schizophrenia. [30][31][32][33] Pharmacological blockade of NMDA receptor function with non-selective NMDA antagonist such as phencyclidine and ketamine can induce temporary psychosis in normal human subjects and provoke symptoms in schizophrenics. 51 GluR1 KO have been found to exhibit a loss of NMDA receptor-mediated long-term potentiation, but normal NMDA-receptorinduced Ca 2 þ influx and NR1 expression, in CA1 hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Previous studies have demonstrated that GluR1 knockout mice (KO) 30 exhibit behavioral abnormalities on tests for cognition, motor function and responses to drugs of abuse. [30][31][32][33][34][35][36][37] In the present study, we sought to extend these data by assessing these mice for a variety of 'schizophrenia-related' phenotypes. In addition, given the wealth of evidence implicating dysfunction of dopamine (DA) neurotransmission in schizophrenia 2 and the major interaction between the dopamine and glutamate systems, 2,38 we evaluated regulation of extracellular striatal DA in GluR1 KO in vivo using high-speed chronoamperometry.…”
Section: Introductionmentioning
confidence: 99%
“…For example, being much smaller than the rat, the mouse is less well able to tolerate the deprivation schedules that can be essential to motivate reliable response rates. However, excellent progress is nonetheless being made in adapting benchmark tests of learning for use in the mouse (Schmitt et al 2003(Schmitt et al , 2004Deacon 2006;Bonardi et al 2010). Mice remain the species of choice for studies of the effects of genetic modifications and cognitive effects have been clearly demonstrated in relation to genotype (Schmitt et al 2003(Schmitt et al , 2004.…”
Section: Replacementmentioning
confidence: 99%
“…However, excellent progress is nonetheless being made in adapting benchmark tests of learning for use in the mouse (Schmitt et al 2003(Schmitt et al , 2004Deacon 2006;Bonardi et al 2010). Mice remain the species of choice for studies of the effects of genetic modifications and cognitive effects have been clearly demonstrated in relation to genotype (Schmitt et al 2003(Schmitt et al , 2004. However, for studies that manipulate neural activity directly, the smaller brain of the mouse can make some brain lesions and injections harder to restrict to their intended locations than is the case in the rat.…”
Section: Replacementmentioning
confidence: 99%